Cultural intelligence on perceived value and satisfaction of ethnic minority groups' restaurant experiences in Korea. Issue 4 (4th July 2019) - Han, Soomi; Yoon, Jiyoung
ABSTRACT: The purpose of this study is to examine ethnic minority groups' understanding of Korean culture through cultural intelligence (CQ), and its effects on perceived value and satisfaction of their Korean restaurant experiences. Data were collected from 232 people, ethnic minority groups who live in Korea with their original nationality. This study discovered that ethnic minority groups with higher cultural intelligence had higher service excellence, economic, and emotional value. The escapist, service excellence, economic, and emotional variables in perceived value had significant results, as the values were positive, customer satisfaction were positive. Among moderating effects of gender, nationality, and residential period, only gender and residential period were partially supported. The residential period of ethnic minority groups illustrated that respondents who had longer experience in Korea, had higher level of CQ. This study aims to provide fundamental information on ethnic minority groups, cultural intelligence and their values when visiting Korean restaurants.